Knowledge, attitudes, and practices toward COVID-19 prevention in Yemen: a community-based cross-sectional study - Hassan, Ola El Hajj; Al-Aghbari, Ahmed Asa’ad; McGowan, Maureen; Dar Iang, Maureen; Basaleem, Huda Omer; Al-Sakkaf, Khaled Abdulla; Hyzam, Dalia; Jahn, Albrecht; Dureab, Fekri (Frontiers in Public Health, 2023)
Background Pandemics, especially in fragile war-torn countries like Yemen, challenge their already strained health systems. Community adherence to pandemic prevention measures is necessary to curb the severity and spread of emerging pandemics – which is influenced by factors, such as people’s knowledge and attitudes toward the pandemic. No studies in Aden have been published on the communities’ knowledge, attitudes, and practices (KAP) toward COVID-19 prevention to date. To understand adherence to pandemic prevention measures in contexts with fragile health systems, this study investigated KAP of Yemeni participants toward the COVID-19 pandemic. Methods We conducted face-to-face semi-structured questionnaires among 400 eligible participants whom were identified for participation in this study through systematic household sampling from eight districts in Aden, Yemen. Eligible participants were Yemeni community members who were ≥ 18 years, living for more than 10 years in Yemen, and were willing to voluntarily participate in the study. The questionnaire included questions surrounding the participants’ COVID-19 knowledge (e.g., awareness of spread and prevention), attitudes (e.g., willingness to accept the vaccine or other prevention measures), and prevention practices during the pandemic (e.g., mask wearing, social distancing, vaccine uptake). Total KAP scores were calculated. Univariate and bivariate statistical analyses were conducted using STATA 13 software. Results From January to May 2021 we conducted 400 questionnaires with Yemeni community members. The average age was 41.5 ± 14.5 years (range 18–86 years). The results demonstrated that the participants in this study had an intermediate knowledge (53%) and fair attitude (58%) scores. However, participants reported very poor COVID-19 prevention practices- with only 11% demonstrating these practices. Only 25% (100/400) practiced social distancing, 25% (98/400) wore a mask, and only 6% (27/400) of participants accepted (at least one dose of) the COVID-19 vaccine. Factors associated with increased knowledge were being male, married, and surprisingly those having a primary and middle school education levels (p < 0.05). Also participants who were diagnosed with COVID-19 or had a family member diagnosed with COVID-19 (vs. those not diagnosed OR = 2.08, 95% CI 1.07–3.78, p < 0.05) were more likely to know that the vaccine protects against severe COVID-19 infection and were more likely to apply good practices such as accepting the vaccine (OR = 2.65, 95% CI 1.17–6.00, p < 0.05) compared to those who were not. Conclusion These findings raise awareness for the need of community-oriented education programs for COVID-19 which considers associated factors to improve the level of public knowledge, attitudes, and practices.